Glucagon-like Peptide-1 Levels and Related Parameters in Rheumatoid Arthritis Patients Prone to Atherosclerosis - Shafeeq, Noorhan K.; Al-joda, Ban Mahmood Shaker; Ala, a, Tamara (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study aimed to estimate the role of glucagon-like peptide-1 (GLP-1) and visfatin as a novel pro inflammatory marker in Rheumatoid Arthritis (RA ) according to the activity scores of disease to assess the possibility of introducing glucagon-like peptide-1 and visfatin in the diagnosis and monitoring of RA patients and to found the correlation of visfatin level with GLP-1 and AIP in patients prone to atherosclerosis ,fifty healthy individuals as control group (G1) and fifty rheumatoid arthritis (RA) patients (G2) were enrolled in this study with middle age ranged (30 â€“ 40) years and BMI â‰¥24 kg/m2. ESR ,RF, lipid profile, CRP,insulin, visfatin and GLP-1were determined. Results in table (1) revealed highly significant increase in ESR,RF,TC,TG,LDL,VLDL and AIP level in rheumatoid arthritis (G2) comparing to (G1) while significant decrease noticed in (G2) group comparing to (G1). Results in table(2) showed highly significant increase in insulin ,CRP, visfatin and GLP-1 level Results in table(3) illustrated correlation relation data and results revealed highly significant ,were r=0.035 for GLP-1 with visfatin for (G1), and highly significant , r= -0.089 for (G2) as shown in figure(1-A) and(1-B), the result also highly significant were r= -0.183 for GLP-1 with CRP for control group and significant ,r= 0.043 for GLP-1 with CRP for RA group as shown in figure(2-A) and(2-B), and significant, r= -0.056 for GLP-1with AIP for G1 and no significant, were r= 0.042 for GLP-1 with AIP for G2 as shown in figure (3-A)and (3-B). conclusion that summarized from this study is glucagon-like peptide-1 and visfatin plays a role in RA pathogenesis that can be considered marker in RA . and may be used as a drug in future for RA patients.